2004
DOI: 10.1021/ol049692c
|View full text |Cite
|
Sign up to set email alerts
|

Unsymmetrical Diaryl Sulfones through Palladium-Catalyzed Coupling of Aryl Boronic Acids and Arylsulfonyl Chlorides

Abstract: [reaction: see text] A simple and efficient method for the synthesis of unsymmetrical diaryl sulfones using the palladium-catalyzed coupling of aryl boronic acids and arylsulfonyl chlorides has been developed. High product yields, a short reaction time, and mild reaction conditions are important features of this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(56 citation statements)
references
References 24 publications
1
52
0
3
Order By: Relevance
“…More recently, both Cu-and Pd-catalyzed couplings of sulfinate anions with aryl halides have also been reported as a means to generate unsymmetrical diaryl sulfones, which are common motifs in bioactive molecules [38,93,[144][145][146][147][148]. Similarly, Cu-catalyzed coupling of arylboronic acids with sulfinate anions has been reported [95,149,150]. Notably, Kantam and co-workers found that the use of ionic liquids permits Cu(OAc) 2 -catalyzed sulfone synthesis at ambient temperature and with convenient product separation and catalyst recyclability (17) [150].…”
Section: Equation 16mentioning
confidence: 99%
“…More recently, both Cu-and Pd-catalyzed couplings of sulfinate anions with aryl halides have also been reported as a means to generate unsymmetrical diaryl sulfones, which are common motifs in bioactive molecules [38,93,[144][145][146][147][148]. Similarly, Cu-catalyzed coupling of arylboronic acids with sulfinate anions has been reported [95,149,150]. Notably, Kantam and co-workers found that the use of ionic liquids permits Cu(OAc) 2 -catalyzed sulfone synthesis at ambient temperature and with convenient product separation and catalyst recyclability (17) [150].…”
Section: Equation 16mentioning
confidence: 99%
“…22.6,29.0,29.2,29.4,29.4,29.5,29.8,31.8 (CH 2 (12), 400 (28), 383 (10), 372 (32), 331 (10), 329 (23), 301 (12), 289 (21), 288 (100), 287 (38), 274 (16), 261 (13), 260 (20). 24 H 32 O 5 S: 432.19650; found: 432.196759.…”
Section: Methyl 2-hydroxy-6-methyl-3-nonyl-5-(phenylsulfonyl)benzoatementioning
confidence: 99%
“…18 In recent years, transition-metal-mediated syntheses of diaryl sulfones have been developed. Examples include the copper(I) iodide/proline mediated reaction of aryl iodides with sodium benzenesulfinate, 19 the Suzuki reaction of 4-methoxybenzeneboronic acid with benzenesulfonyl chloride, 20 and the copper(II) acetate catalyzed reaction of 4-methoxybenzeneboronic acid with sodium benzenesulfinate (in the presence of 1,10-phenanthroline and oxygen). 21 Despite their great synthetic utility, the sulfonations outlined above, which all rely on the coupling of two arene moieties, can suffer from several drawbacks, such as harsh reaction conditions, low regioselectivity, and narrow synthetic scope.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5,6] In response to these limitations, the use of transitionmetal-catalyzed cross-coupling has been exploited as a route to sulfones. [7] The most utilized has been copper catalysis, in which sodium sulfinates couple with aryl, heteroaryl, or alkenyl halides, [8] or boronic acids.…”
mentioning
confidence: 99%